2017
DOI: 10.1103/physrevlett.119.075902
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally Strong Phonon Scattering by B Substitution in Cubic SiC

Abstract: We use ab-initio calculations to predict the thermal conductivity of cubic SiC with different types of defects. An excellent quantitative agreement with previous experimental measurements is found. The results unveil that BC substitution has a much stronger effect than any of the other defect types in 3C-SiC, including vacancies. This finding contradicts the prediction of the classical massdifference model of impurity scattering, according to which the effects of BC and NC would be similar and much smaller tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 46 publications
(43 reference statements)
8
104
1
Order By: Relevance
“…It is important to note how the present case is very different from our previous work on SiC. 34,35 In the present work, we observe a significant contribution of both EPS and PDPS to κ of a highly-doped system; whereas in our previous work we observed that PDPS was sufficient on its own to correctly predict the κ of B-doped cubic SiC owing to the resonant phonon scattering that boron causes. 34,35 The resonant scattering was at least one to two orders of magnitude higher than that caused by other defects and resulted in a drastic reduction (approximately two orders of magnitude at room temperature) in the thermal conductivity even at relatively mod- est defect concentrations (≈ 10 20 cm −3 ).…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…It is important to note how the present case is very different from our previous work on SiC. 34,35 In the present work, we observe a significant contribution of both EPS and PDPS to κ of a highly-doped system; whereas in our previous work we observed that PDPS was sufficient on its own to correctly predict the κ of B-doped cubic SiC owing to the resonant phonon scattering that boron causes. 34,35 The resonant scattering was at least one to two orders of magnitude higher than that caused by other defects and resulted in a drastic reduction (approximately two orders of magnitude at room temperature) in the thermal conductivity even at relatively mod- est defect concentrations (≈ 10 20 cm −3 ).…”
Section: Resultscontrasting
confidence: 87%
“…Neither EPS nor PDPS can be captured by conventional parameterized models. Together with our previous works on doping diamond, SiC, GaN and GaAs, 34,[36][37][38] we show that, at temperatures above 300 K, PDPS is the most dominant scattering mechanism in highly B-and P-doped Si and cannot be neglected.…”
Section: Discussionsupporting
confidence: 80%
“…The scattering due to local, static strain (η) depends on the anharmonicity of the distorted bonds, as captured in the Grüneisen parameter (γ). Notably, both the ∆K and ∆R effects are captured in the changes to the DFT-calculated interatomic force constants, which change locally in response to both structural relaxation and an altered chemical environment 13 . Additionally, the strain scattering strength is scaled by the coefficient Q, which approximates the number of distorted nearest neighbor bonds around a point defect.…”
Section: /17 3 Model Derivation: Umklapp and Point Defect Scatteringmentioning
confidence: 99%
“…These simulations have shown very good quantitative agreement with experiments for a range of materials and have provided useful insights regarding the mechanisms of phonon-defect scattering 10,11 . However, multiple calculations are required to compute defect structures, evaluate scattering strengths, and solve the Boltzmann transport equation for the thermal conductivity [12][13][14][15] . Often, these techniques are too expensive and system dependent for routine modelling used to determine the dominant scattering mechanisms in a system 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the wavelengths of thermal phonons are usually many times of the lattice spacing, the scattering of thermal phonons by a point defect is often considered as Rayleigh scattering and exhibits very weak scattering strength for low frequency phonons.The Rayleigh scattering is well captured by models suggested by Klemens [14] and Tamura [15], which assume that the change in mass and interatomic force constants (IFCs) by a point defect is limited to a single lattice site. The recently developed ab initio Green's function approach [16,17] also shows the Rayleigh scattering behavior for strongly bonded materials, such as diamond and BAs [18][19][20][21][22][23][24].In this report, we show that the point defects in IV-VI semiconductors (PbTe and GeTe), unlike the previously studied strongly bonded materials, cause Mie scattering of thermal phonons. The IV-VI semiconductors are widely used for the applications of thermoelectrics and phase change materials where the thermal conductivity is a key parameter for the device figure-of-merit.…”
mentioning
confidence: 50%